Crucial factors preceding compulsory psychiatric admission: a qualitative patient-record study - de Jong, Mark H. (BMC Psychiatry, 2017)
BACKGROUND: Compulsory admissions have a strong effect on psychiatric patients and represent a deprivation of personal liberty. Although the rate of such admissions is tending to rise in several Western countries, there is little qualitative research on the mental health-care process preceding compulsory admission. The objective of the study was to identify crucial factors in the mental health-care process preceding compulsory admission of adult psychiatric patients. METHODS: This retrospective, qualitative multiple-case study was based on the patient records of patients with severe mental illness, mainly schizophrenia and other psychotic disorders. Twenty two patient records were analyzed. Patients’ demographic and clinical characteristics were heterogeneous. All were treated by Flexible Assertive Community Treatment teams (FACT teams) at two mental health institutions in the greater Rotterdam area in the Netherlands and had a compulsory admission in a predefined inclusion period. The data were analyzed according to the Prevention and Recovery System for Monitoring and Analysis (PRISMA) method, assessing acts, events, conditions, and circumstances, failing protective barriers and protective recovery factors. RESULTS: The most important patient factors in the process preceding compulsory admission were psychosis, aggression, lack of insight, care avoidance, and unauthorized reduction or cessation of medication. Neither were health-care professionals as assertive as they could be in managing early signs of relapse and care avoidance of these particular patients. CONCLUSION: The health-care process preceding compulsory admission is complex, being influenced by acts, events, conditions and circumstances, failing barriers, and protective factors. The most crucial factors are patients’ lack of insight and cessation of medication, and health-care professionals’ lack of assertiveness. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12888-017-1512-y) contains supplementary material, which is available to authorized users.